1999
DOI: 10.1097/00001786-199904000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of a Hospital's Pain Management Program

Abstract: Nationally, the focus on facilities providing effective pain management has increased, yet no funds have been allocated to pain management programs. The article describes a 3-year study whose purpose was to evaluate the effect on nurses' attitudes and behavior of the institution of a multifaceted, low-cost hospital pain management program. The program utilized various instructional methods and implementation of policies, procedures, and documentation protocols. Nurses were surveyed before and after the pain ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…In addition, an optimal assessment would enhance positive communication between professionals in which all parties perceive the accurate level and tolerance of patient while he/she undergoes any medical procedure [11, 12, and 13]. Stratton [18] (1999) conducted a 3-year study examining the effectiveness of a pain monitoring program. Nurses' attitudes and behaviors towards pain assessment, interventions, and documentation were assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an optimal assessment would enhance positive communication between professionals in which all parties perceive the accurate level and tolerance of patient while he/she undergoes any medical procedure [11, 12, and 13]. Stratton [18] (1999) conducted a 3-year study examining the effectiveness of a pain monitoring program. Nurses' attitudes and behaviors towards pain assessment, interventions, and documentation were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the knowledge base and attitudes of nurses regarding multiple aspects of pain management are important factors to promote patients' feeling of effective pain management. A specialized pain training programs have improved nurses' ability to develop optimal care plans that are inherited with frequent assessment starting from admission to discharge [18]. However, the majority of evidence concerned with nursing practice in pain management emerged from United States, England, and Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of pain as the "fifth vital sign" (Stratton 1999, 11) could assist nurses with assessing and documenting pain with the same frequency as they monitor other vital signs such as heart rate, respiratory rate, temperature, and blood pressure (Stratton;Wilsey et al 2004). This may help nurses with learning to value, accept, and validate patients' reports of pain (Buckley 2000).…”
Section: Discussionmentioning
confidence: 99%
“…16 This, along with an absence of adequate education on the part of healthcare consumers and providers and an absence of standards and guidelines for care, makes reliable identification and treatment of persistent pain difficult. 9,21 In consequence, care management strategies used to identify and screen potential populations and then implement individualized treatment plans have great potential for addressing the needs of this underserved population. On a clinical level, it is imperative that both healthcare practitioners and consumers become more aware of the issues surrounding persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…Care management involves an interdisciplinary coordination of services with a focus on maximizing individuals' functioning and independence. 8 As persistent pain is often under-or inappropriately treated, 3,9 care management provides a method through which to identify a population at risk and to integrate individualized treatment across populations, conditions, and delivery systems. After a selected population is risk-or severity-stratified, appropriate care management interventions can then be targeted to individuals and groups in a cost-effective manner.…”
Section: Introduction Pmentioning
confidence: 99%